Minimally invasive liver resection: has the time come to consider robotics a valid assistance? - Caruso, Stefano; Patriti, Alberto; Ceccarelli, Graziano; Coratti, Andrea (HepatoBiliary Surgery and Nutrition; Vol 7, No 3 (June 21, 2018): Hepatobiliary Surgery and Nutrition, 2018)
Minimally invasive liver resection (MILR) has been steadily increasing worldwide. Since its introduction in the early 1990s, initially adopted in cases of wedge and minor anatomical resection for benign hepatic lesions, MILR has been extended to major liver resection and for malignant hepatic lesions (1). Laparoscopic lateral sectionectomy has progressively become a standard operation (2).